Development of an electrostatic charge based device for visualization of the latent fingerprint on bullet cartridges and curved metallic surfaces - Lu, Jilun. (2011)
Fingerprinting is an effective method used in identification of persons. As the chances of an individual having the same set of fingerprints is extremely low – 1 in 64 billion, the unique characteristics of fingerprints has allowed investigators to use it for the purpose of identification, making fingerprints an integral part of law enforcement process.